Calcaneal osteoid osteoma hidden by confusing symptoms in a 18 years old basketball player: a case report - Rondoni, A.; Francini, L. (Journal of Sports Medicine & Doping Studies, 2015)
Osteoid osteoma is a small common benign osteoblastic tumor. Foot osteoid osteomas represent a minority of cases. Patients are usually male children and young adults within the third decade. In our case report we describe an osteoid osteoma of the calcaneus in a young adult, semi-professional basketball player. Starting from the case description, we aim to: 1) Analyse the reasons of initial misdiagnosing, also due to misleading previous sport injury, and potential mimickers, 2) Discuss the different conservative and surgical therapeutic options.